Inhibition of non-NMDA ionotropic glutamate receptors delays the retinal degeneration in rd10 mouse. (1st September 2018) - Xiang, Zongqin; Bao, Yiqin; Zhang, Jia; Liu, Chao; Xu, Di; Liu, Feng; Chen, Hui; He, Liumin; Ramakrishna, Seeram; Zhang, Zaijun; Vardi, Noga; Xu, Ying
Abstract: Retinitis pigmentosa (RP) is a hereditary blinding disease characterized by neurodegeneration of photoreceptors. Retinal ganglion cells (RGCs) in animal models of RP exhibit an abnormally high spontaneous activity that interferes with signal processing. Blocking AMPA/Kainate receptors by bath application of CNQX decreases the spontaneous firing, suggesting that inhibiting these receptors in vivo may help maintain the function of inner retinal neurons in rd10 mice experiencing photoreceptor degeneration. To test this, rd10 mice were i.p. injected with CNQX or GYKI 52466 (an AMPA receptor antagonist) for 1–2 weeks, and examined for their retinal morphology (by immunocytochemistry), function (by MEA recordings) and visual behaviors (using a black/white box). Our data show that iGluRs were up-regulated in the inner plexiform layer (IPL) of rd10 retinas. Application of CNQX at low doses both in vitro and in vivo, attenuated the abnormal spontaneous spiking in RGCs, and increased the light-evoked response of ON RGCs, whereas GYKI 52466 had little effect. CNQX application also improved the behavioral performance. Interestingly, in vivo administration of CNQX delayed photoreceptor degeneration, evidenced by the increased cell number and restored structure. CNQX also improved the structure of bipolar cells. Together, we demonstrated that during photoreceptor degeneration, blockade of the non-NMDA iGluRs decelerates the progression of RGCs dysfunction, possibly by dual mechanisms including slowing photoreceptor degeneration and modulating signal processing within the IPL. Accordingly, this strategy may effectively extend the time window for treating RP. Highlights: AMPA/KA receptors are upregulated in the inner plexiform layer of rd10 retina. Blocking AMPA/KAR with CNQX in vitro improves function of rd10 ganglion cells. Treating rd10 mice with CNQX improves function of rd10 ON ganglion cells. CNQX improves visual behavior of rd10 mice. CNQX improves the structure of photoreceptors and bipolar cells in rd10 retina.